Three-dimensional Propagation of the Global Extreme-ultraviolet Wave Associated with a Solar Eruption on 2021 October 28 - Hou, Zhenyong; Tian, Hui; Wang, Jing-Song; Zhang, Xiaoxin; Song, Qiao; Zheng, Ruisheng; Chen, Hechao; Chen, Bo; Bai, Xianyong; Chen, Yajie; He, Lingping; Song, Kefei; et al. (The Astrophysical journal, 2022)
We present a case study for the global extreme-ultraviolet (EUV) wave and its chromospheric counterpart the Moreton-Ramsey Wave associated with the second X-class flare in Solar Cycle 25 and a halo coronal mass ejection (CME). The EUV wave was observed in the H α and EUV passbands with different characteristic temperatures. In the 171 Å and 193/195 Å images, the wave propagates circularly with an initial velocity of 600–720 km s −1 and a deceleration of 110–320 m s −2 . The local coronal plasma is heated from log( T/K ) ≈ 5.9 to log( T/K ) ≈ 6.2 during the passage of the wave front. The H α and 304 Å images also reveal signatures of wave propagation with a velocity of 310–540 km s −1 . With multiwavelength and dual-perspective observations, we found that the wave front likely propagates forwardly inclined to the solar surface with a tilt angle of ∼53°.2. Our results suggest that this EUV wave is a fast-mode magnetohydrodynamic wave or shock driven by the expansion of the associated CME, whose wave front is likely a dome-shaped structure that could impact the upper chromosphere, transition region, and corona.